2004
DOI: 10.1002/ange.200490026
|View full text |Cite
|
Sign up to set email alerts
|

Titelbild: Fünfkernige Platin(II)‐Makrocyclen mit Nucleobasen (Angew. Chem. 10/2004)

Abstract: Metallocalixarene wie der im Titelbild gezeigte fünfkernige Platin(II)‐Makrocyclus wurden aus einem Cisplatin‐Analogon mit tertiären Aminliganden und der Nucleobase Uracil oder Thymin aufgebaut. Der für die Synthese dieser Makrocyclen eingesetzte Platin(II)‐Komplex zeigt aufgrund seiner Bindung an die DNA signifikante cytostatische Aktivität. Im Hintergrund ist ein Kristall von DNA aus Kalbsthymus dargestellt. Details zu diesem neuartigen Strukturtyp erfahren Sie in der Zuschrift von B. Krebs und M. J. Rauterk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The smallest ring size with pym ligands is n = 3. [8] Structurally characterized examples of metallacalix [n]arenes with the pym nucleobases uracil (H 2 U), thymine (H 2 T), and cytosine (H 2 C) thus far include species with n = 3, [9] 4, [4,10] and 8. [10] With the C 2v -symmetric 2-dmpymo anion a cyclic hexanuclear species has Abstract: Pyrimidine (pym) ligands with their two endocyclic N-donor atoms provide 1208 angles for molecular constructs, which, with the 908 angle metal fragments cis-a 2 M II (M = Pt, Pd; a = NH 3 or a 2 = diamine), form cyclic complexes known as metallacalix [n]arenes (with n = 3, 4, 6, 8, …).…”
Section: Introductionmentioning
confidence: 99%
“…The smallest ring size with pym ligands is n = 3. [8] Structurally characterized examples of metallacalix [n]arenes with the pym nucleobases uracil (H 2 U), thymine (H 2 T), and cytosine (H 2 C) thus far include species with n = 3, [9] 4, [4,10] and 8. [10] With the C 2v -symmetric 2-dmpymo anion a cyclic hexanuclear species has Abstract: Pyrimidine (pym) ligands with their two endocyclic N-donor atoms provide 1208 angles for molecular constructs, which, with the 908 angle metal fragments cis-a 2 M II (M = Pt, Pd; a = NH 3 or a 2 = diamine), form cyclic complexes known as metallacalix [n]arenes (with n = 3, 4, 6, 8, …).…”
Section: Introductionmentioning
confidence: 99%
“…In this study we have demonstrated that the "directed" assembly of metallacalix [4]arenes containing the parent pyri- midine nucleobase cytosine also occurs when a cis-[Pt-…”
Section: Discussionmentioning
confidence: 97%
“…[2] The cations of cis- Figures 14 and 15, respectively. The molecular metallacalix [4]arene skeleton formed Scheme 3. Relationship between mononuclear 1, tetranuclear 5, and octanuclear 6 and 7.…”
Section: Inverting Metals Inmentioning
confidence: 99%
See 2 more Smart Citations